RF21 Living with multimorbidity in ghana: a qualitative study guided by the cumulative complexity model. (September 2018) - Morgan, SA; Eyles, C; Roderick, PJ; Adongo, P; Hill, AG
Abstract : Background: Defined as the co-occurrence of more than two chronic conditions, multimorbidity has been described as a significant health-care problem: a trend linked to a rise in non-communicable disease and an ageing population. Evidence on the experiences of living with multimorbidity in middle-income countries (MICs) is limited. In higher income countries (HICs), multimorbidity has a complex impact on health outcomes, including functional status, disability and quality of life, complexity of healthcare and burden of treatment. Methods: This study aimed to explore the perceptions and experiences of women living with multimorbidity in the Greater Accra region, Ghana: to understand the complexity of their health needs due to multimorbidity, and to document how the health system responded. Guided by the cumulative complexity model, and using stratified purposive sampling, 20 in-depth interviews were conducted across three polyclinics in the Greater Accra region. The data was analysed using the six phases of Thematic Analysis. Results: Overall four themes emerged: 1) the influences on their health experience; 2) seeking care and the responsiveness of the healthcare system; 3) how patients manage healthcare demands; and 4) outcomes due to health. Spirituality and the stigmatisation caused by specific conditions, such as HIV, impacted their overall health experience. Women depended on the care and treatment provided through the healthcare system despite inconsistent coverage and a lack of choice thereof; although their experiences varied by chronic condition. Women depended on their family and community to offset the financial burden of treatment costs, which was exacerbated by having many conditions. Conclusion: The implications are that integrated health and social support, such as streamlining procedures and professional training on managing complexity, will benefit and reduce the burden of multimorbidity experienced by patients with multimorbidity in Ghana.